Prognostic value of the left ventricular ejection fraction reserve acquired by gated myocardial perfusion SPECT in patients with CAD and reduced stress LVEF - Zhang, Shuang; Meng, Jingjing; Zhou, Yihan; Lv, Lijun; Zhang, Xiaoli (Frontiers in Cardiovascular Medicine, 2024)
Purpose: Left ventricular ejection fraction (LVEF) strongly predicts cardiac events. However, conflicting findings exist regarding the prognostic value of the LVEF reserve (△LVEF) when measured by gated single-photon emission computed tomography myocardial perfusion imaging (SPECT G-MPI). In particular, data related to the prognostic value of △LVEF when measured by SPECT in patients with reduced LVEF are scarce. In this study, we aimed to evaluate the prognostic value of △LVEF when acquired by SPECT G-MPI in patients with coronary artery disease (CAD) and a LVEFStress < 60%. Methods: We retrospectively recruited 260 consecutive patients diagnosed with CAD by coronary angiography (CAG) and a LVEFStress < 60%, as determined by SPECT G-MPI. These patients were followed up for 33.4 ± 7.6 months. The patients were divided into two groups (△LVEF > 0% and △LVEF ≤ 0%), and survival analyses were conducted. The primary endpoints were major adverse cardiac events (MACEs), a composite of all-cause death, nonfatal myocardial infarction, unplanned coronary revascularization, and hospitalization for unstable angina. Results: We observed 69 MACEs (26.5%). The cumulative incidence of MACEs in patients with △LVEF ≤ 0% was significantly higher than in patients with △LVEF > 0% (P = 0.042). Multivariate Cox regression further revealed that a △LVEF ≤ 0% represented an independent predictor of MACEs (adjusted hazard ratio [HR]: 1.276; 95% confidence interval [CI]: (1.006, 1.618), P = 0.045). Adding a △LVEF ≤ 0% to traditional myocardial perfusion and function variables evaluated by MPI significantly improved the ability to predict MACEs (P = 0.044). Conclusions: Determining △LVEF by SPECT G-MPI was associated with MACEs and improved risk stratification compared to prediction models based on traditional perfusion and functional parameters in CAD patients with left ventricular dysfunction, particularly those with no or mild myocardial ischemia.Coronary artery bypass graft CAD Coronary artery disease CAG Coronary angiography EDV End-diastolic volume ESV End-systolic volume LVEF Left ventricular ejection fraction MACEs Major adverse cardiac events MPI Myocardial perfusion imaging PCI Percutaneous coronary intervention PET Positron emission computed tomography SPECT Single-photon emission computed tomography TID Transient ischemic dilatation TPD Total perfusion defect △LVEF Left ventricular ejection fraction reserve 1